Compétitivité acquise et capacité d’adaptation : l’agriculture pampéenne face à la crise - Guillermo Hillcoat; Martine Guibert (Cahiers des Amériques Latines)
In the political, social and economic chaos which began in Argentina in December 2001, pampas agriculture benefited from some of the measures arising from the economic conditions, such as devaluation. However, it also suffered from a heavy fiscal load (the return of retentions on exportations) and debts which sometimes led to the bankruptcy of smaller producers. The 21st century therefore begins with signs of uncertainty, after the 1990s synonymous with stability and advances in productivity.